2019
DOI: 10.1016/j.powtec.2019.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of alumina powder mixtures investigated using shear tests

Abstract: The flow properties of alumina powder mixtures have been investigated using shear tests on a powder rheometer. The evolution of the flow index, ff c , as a function of the powder mixture composition show that all the points form a single curve whatever the pre-shear consolidation stress value adopted, the mixing conditions and the preconditioning of the powder bed (relative humidity) before the tests. It has been also shown that the flow properties of the mixtures are controlled by the competition between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…Moreover, the PGB takes into account the whole particle size distribution of polydispersed powders while most of the previous models used mean or median diameters to represent the particle size. The correlation represented by equation (1) has also been observed experimentally using ceramic powders by Bernard-Granger who attempted to take into account the capillary forces in the PGB calculations [7]. Finally, Giraud also extended the model to other powders and showed that the empirical equation 1was actually consistent with Rumpf's theory [8].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, the PGB takes into account the whole particle size distribution of polydispersed powders while most of the previous models used mean or median diameters to represent the particle size. The correlation represented by equation (1) has also been observed experimentally using ceramic powders by Bernard-Granger who attempted to take into account the capillary forces in the PGB calculations [7]. Finally, Giraud also extended the model to other powders and showed that the empirical equation 1was actually consistent with Rumpf's theory [8].…”
Section: Introductionsupporting
confidence: 59%
“…This multi-component dimensionless Bond number was shown to correlate well with the flow function coefficient measurements, according to equation 1, for mixtures composed of pharmaceutical powders [6] and ceramic oxide powders [7] even if the and empirical parameters of the correlation varies among the authors. However, these differences could be explained by the density of the powders investigated and also by the flow function coefficient measurement protocol [8].…”
Section: Introductionmentioning
confidence: 73%
“…Such a correlation has also been verified experimentally by investigating the rheological behavior of powder mixtures constituted by different amounts of two alumina powders (Bernard-Granger et al, 2019).…”
Section: àB ð6þmentioning
confidence: 66%
“…Since most investigations focus only on the Van der Waals force contributions for the calculation of interparticle forces, Bernard-Granger attempted to take also into account the capillary forces in the calculation of the granular Bond number (Bernard-Granger et al, 2019). However, this study was done with alumina powders that appear to be sparsely sensitive to relative humidity.…”
Section: àB ð6þmentioning
confidence: 99%
See 1 more Smart Citation